Efficient n-type doping in epitaxial graphene through strong lateral orbital hybridization of Ti adsorbate. (November 2016) - Chen, Jhih-Wei; Huang, Hao-Chun; Convertino, Domenica; Coletti, Camilla; Chang, Lo-Yueh; Shiu, Hung-Wei; Cheng, Cheng-Maw; Lin, Ming-Fa; Heun, Stefan; Chien, Forest Shih-Sen; Chen, Yi-Chun; Chen, Chia-Hao; et al.
Abstract: In recent years, various doping methods for epitaxial graphene have been demonstrated through atom substitution and adsorption. Here we observe by angle-resolved photoemission spectroscopy (ARPES) a coupling-induced Dirac cone renormalization when depositing small amounts of Ti onto epitaxial graphene on SiC. We obtain a remarkably high doping efficiency and a readily tunable carrier velocity simply by changing the amount of deposited Ti. First-principles theoretical calculations show that a strong lateral (non-vertical) orbital coupling leads to an efficient doping of graphene by hybridizing the 2 p z orbital of graphene and the 3 d orbitals of the Ti adsorbate, which attached on graphene without creating any trap/scattering states. This Ti-induced hybridization is adsorbate-specific and has major consequences for efficient doping as well as applications towards adsorbate-induced modification of carrier transport in graphene.